TRANSPORTASI ONLINE VS TRANSPORTASI TRADISIONAL NON-ONLINE PERSAINGAN TIDAK SEHAT ASPEK PEMANFAATAN APLIKASI OLEH PENYELENGGARA ONLINE (Lex Jurnalica, 2016)
AbstractInformation technological advances that have resulted makes disruption in various business sectors. Among the shaken is the pattern of field ground transportation business ventures include the other fields business sector. No one is untouched by advances in information technology so that the patterns of trying to be more efficient than the pattern of previous efforts. The existence of legal subjects that had been willed to be incorporated for the sake of efficiency and the business's security is also challenged its existence. Turns to subjek law individuals can conduct business through the use of information technology such as the emergence of on-line stores, online transportation and other online businesses. The facilities and a variety of features as well as start-up provided by the service provider application provider is quite varied. Individual persons as legal subjects experienced only stayed open an account and ready to run a business like stores on line that have been run and successfully run a business. Thus Agency Limited Liability Company, which has been the choice of doing business is not a viable option anymore priority. Governments need to review and reset all settings regulation that are friendly with the advancement of information technology. The pattern of competition in various business sectors also face shifting from physical to non physical paced non-face virtually. Draw together the individual legal subjects and legal subjects legal entities doing business on line by way of non online less precise and be not a requirement. Putting the competition non on line with on line are not placed in the same setting. The setting must be distinguished in the regulation of competition in the sphere of fellow on line. Keywords: legal subject, the relationship between the legal subject and competition pattern on line with non on line. AbstrakKemajuan teknologi informasi mengakibatkan guncangan besar dalam dunia bisnis apa pun. Guncangan tersebut terutama terhadap bisnis yang menggunakan aplikasi online. Tidak ada bentuk bisnis yang tidak tersentuh kemajuan teknologi informasi. Teknologi informasi akan menjadikan bisnis lebih efisien dalam menjalankan bisnis. Dapat memotong rantai distribusi yang begitu panjang dari produsen kepada konsumen atau end user. Keberadaan subjek hukum perorangan dalam kegiatan pada bisnis on line semakin terlihat marak. Peranan subjek hukum pribadi natural persoonlijke terlihat dengan munculnya toko-toko online non-korporasi. Karena penyelenggara aplikasi telah menyiapkan kemudahan kemudahan secara aplikasi untuk seseorang menjalankan usaha. Seseorang menjalankan usaha tanpa harus berbentuk korporasi atau harus berbentuk badan hukum. Menjalankan usaha menjadi begitu sederhana setiap orang dapat menjalankan usaha karena aplikasi telah tersedia. Subjek hukum perorangan cukup membuka dan mendaftar account pada penyedia aplikasi. Pola persaingan usahapun menjadi berubah persaingan yang semula hanya terjadi di arena perdagangan secara fisik tatap muka saat kemajuan teknologi informasi berkembang persaingan menjadi persaingan maya. Persaingan yang terjadi bergeser menjadi persaingan maya antara orang yang sama sama menjalankan usaha secara maya. Persaingan tatap muka secara fisik dengan persaingan maya menjadi tidak fair dan memang tidak dapat disandingkan. Seharusnya persaingan yang dapat disandingkan adalah persaingan orang yang menjalankan usaha sesama online tidak online dengan non-online. Kata kunci: subjek hukum, hubungan subjek hukum dan pola persaingan online dan non- online.